Clinical outcomes following robotic versus conventional DIEP flap in breast reconstruction: A retrospective matched study - Lee, Min Jeong; Won, Jongmin; Song, Seung Yong; Park, Hyung Seok; Kim, Jee Ye; Shin, Hye Jung; Kwon, Young In; Lee, Dong Won; Kim, Na Young (Frontiers in Oncology, 2022)
Background: A robotic deep inferior epigastric perforator (DIEP) flap created through a totally extraperitoneal approach minimizes violation of the donor site, which may lead to postoperative pain reduction and rapid recovery. The authors compared the clinical outcomes of robotic and conventional DIEP flap breast reconstructions. Methods: Data from consecutive patients who underwent mastectomy with DIEP flaps for breast reconstruction between July 2017 and January 2021 were retrospectively reviewed. Patients were divided into robotic and conventional DIEP groups, and the two groups were matched using the inverse probability of treatment weighting method. They were compared based on the reconstruction time, drainage amount, postoperative pain, rescue analgesics, hospital stay, complications, and BREAST-Q scores. Results: After matching, a dataset of 207 patients was formed, including 21 patients in the robotic DIEP group and 186 patients in the conventional DIEP group. The mean reconstruction time was longer in the robotic DIEP group than in the conventional DIEP group (P<0.001). In the robotic group, pain intensity during the postoperative 6–24 hours was significantly reduced (P=0.001) with less use of fentanyl (P=0.003) compared to the conventional DIEP group. The mean length of hospital stay for the robotic DIEP group was shorter than that for conventional DIEP (P=0.002). BREAST-Q scores indicated a higher level of the abdominal physical well-being domain in the robotic group (P=0.020). Complication rates were comparable between the two groups. Conclusions: This study suggests that a robotic DIEP flap offers enhanced postoperative recovery, accompanied by a reduction in postoperative pain and hospital stay.